2007
DOI: 10.1002/smll.200700484
|View full text |Cite
|
Sign up to set email alerts
|

Surfactantless Synthesis of Silver Nanoplates and Their Application in SERS

Abstract: Silver nanoplates with thicknesses of 50-70 nm and edge lengths ranging from 200 nm to 1 mum have been grown on semiconductor wafers at room temperature through a simple galvanic reaction between an aqueous solution of AgNO(3) and n-type GaAs. The as-grown Ag structures have chemically clean surfaces due to no surfactant or coordinating molecules being involved in the synthesis. Electron microscopy characterizations indicate that each Ag plate has rough surfaces and a half-moon morphology with one straight edg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 150 publications
(134 citation statements)
references
References 133 publications
2
131
0
1
Order By: Relevance
“…These nanoparticles attract tremendous research interest because of their unique properties and applications that are difficult (or even impossible) to achieve from single-component nanoparticles. [1][2][3][4][5][6] For example, hybrid magnetic/metallic nanoparticles represent an important class of nanomaterials because of applications in, for example, recoverable catalysis, [7] drug delivery, [8] multimodal imaging, and therapy in biomedicine. [9] As a result, the development of facile strategies for the synthesis of such hybrid nanoparticles is very intriguing.…”
mentioning
confidence: 99%
“…These nanoparticles attract tremendous research interest because of their unique properties and applications that are difficult (or even impossible) to achieve from single-component nanoparticles. [1][2][3][4][5][6] For example, hybrid magnetic/metallic nanoparticles represent an important class of nanomaterials because of applications in, for example, recoverable catalysis, [7] drug delivery, [8] multimodal imaging, and therapy in biomedicine. [9] As a result, the development of facile strategies for the synthesis of such hybrid nanoparticles is very intriguing.…”
mentioning
confidence: 99%
“…Alonso et al [41] found that the surface diffusion coefficient of Au atoms would greatly increase after a small amount of KCl was added to a 0.5 m H 2 SO 4 solution, and they proposed that high coverage of Cl À ions on Au helped to form new Au-Cl surface compounds, which enhanced the surface mobility of the Au atoms. Dursun et al [42] have systematically studied the effect of halide ions on the dealloying of Au/Ag alloys in HClO 4 solutions, where they found that the surface diffusivity of the Au atoms increased by one order of magnitude in the mixed 0.1 m HClO 4 /0.1 m KCl solution, leading to an enlarged size scale for the resulting nanoporous structure. They also found that the addition of Cl À could decrease the equilibrium potential for elemental Ag in addition to the reduction of the critical potential for dealloying Au/Ag.…”
Section: Characterization Of Nanoporous Silvermentioning
confidence: 98%
“…Ag nanostructures, such as nanowires, [1] nanorods, [2] nanocubes, [3] nanoplates, [4] and nanodendrites, [5] exhibit interesting structure-dependent physical properties, which are particularly attractive for optical and sensing applications. [6][7][8][9] Meanwhile, Ag nanoparticles with well-defined morphology and geometry have been proven to work as novel template materials for the construction of hollow metallic nanostructures with intriguing structural properties.…”
Section: Introductionmentioning
confidence: 99%
“…I n o rd e r t o c o n f i r m t h e e ff e c t o f microscopic roughness of the individual nanoplates on the superhydrophobicity, we grew Ag nanoplates with very rough surfaces through reaction with AgNO 3 solution with a low concentration of 0.1 mol/L [48]. Figure 3 shows a series of SEM images of the Ag products formed at different growth times.…”
Section: Nano Researchmentioning
confidence: 99%